The Effect of Preoperative Anxiety on Motor and Sensory Block Duration and Effectiveness in Spinal Anesthesia - Yadigar Yılmaz; Esra Durmayuksel; Tuna Erturk; Ferda Yılmaz Inal; Dilek Metin Yamac; Aysin Ersoy (Anesthesiology Research and Practice)
Introduction. The aim was to evaluate the effect of preoperative anxiety on the sympathetic block that developed after spinal anesthesia and therefore the duration of motor and sensory blockade. Materials and Methods. After the approval of the ethics committee, 90 patients between the ages of 18 and 55 years who were to be operated under spinal anesthesia were included in the study. Preoperative anxiety of the patients was evaluated with the Spielberger trait and State Anxiety Scale and Visual Analog Scale (VAS). The Bromage scores of the patients were followed up intermittently. Onset time of sensory block, onset time of motor block, and motor block recovery time were recorded. Cases with bradycardia and hypotension were noted. Results. No statistically significant correlation was found between the duration of motor block onset (5.81 ± 4 min), the sensory block onset time (0.89 ± 0.4 min), and the motor block recovery time (92.06 ± 36.9 min) with other variables. VAS (5.81 ± 2.5), STAI-1 (40.4 ± 9.8), and STAI-2 (41.69 ± 8.2) values had a statistically significant effect on the occurrence of bradycardia (14.4%). The variables of VAS, STAI-1, STAI-2, sensory block onset, motor block onset, and motor block recovery time were statistically significantly higher in women (mean 5.24 ± 2.4, 38.97 ± 9.9, 41.43 ± 8.7, 0.89 ± 0.42, 5.64 ± 3.82, and 88.77 ± 38.74 in males and mean 7.15 ± 2.1, 43.74 ± 8.9, 42.30 ± 7.0, 0.88 ± 0.27, 6.20 ± 4.35, and 99.70 ± 31.70 in females, respectively). Conclusion. It was observed that preoperative anxiety had no effect on motor and sensory block onset and duration.